15 New Testament words of life : a New Testament theology for real life - Gupta, Nijay K. (Grand Rapids, Michigan : : William B. Eerdmans Publishing Company, 2022)
"This book approaches New Testament theology through the New Testament's most important words, including gospel, life, faith, forgiveness, and others. You will learn what these important words meant to the earliest Christians and also how we can capture the transformative power of these 15 words to live faithfully for Christ in God's world"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher
Keywords: Bible. -- Terminology; Bible. -- Theology; Theology, Doctrinal -- Popular works